An Investigation of Expressionist Ideas of Contemporary Persian Female Poets - Naser Alizadeh; Fatemeh Manavi (مطالعات زبانی و بلاغی)
Expressionism or Constructionism is a school in literature, painting, and cinema in the early twentieth century in Germany. Expressionism in literature is the way that looks at the world through emotions which can be a sign of reaction and romantic desires of artists who lived in industrial and developing societies in the early twentieth century. Moreover, they aimed at providing a definition of capitalist society in order to challenge the various crises rejecting the traditional models in order to set the ground for human freedom. On the other hand, since expressionism has a social and cultural perspective on human life, it affects different literary issues especially linguistic and rhetorical aspects. This article attempts to briefly describe the characteristics of the Expressionist school and scrutinize the samples of poems by Persian famous female poets including Parvin Etesami, Forough Farrokhzad, Simin Behbehani, Zhaleh Esfahani, and Taherh Saffarzadeh based on this approach.